Posterior reversible encephalopathy syndrome after augmentation cystoplasty in a child with neurogenic bladder - Mudasir Ahmad Magray; Gowhar Nazir Mufti; Nisar Ahmad Bhat; Aejaz Ahsan Baba; Mudasir Hamid Buch; Faheem Ul Hasan; Shahid Bashir Banday (Wolters Kluwer Medknow Publications, 2018)
Posterior reversible encephalopathy syndrome (PRES) or leukoencephalopathy syndrome was introduced into clinical practice in 1996 by Hinchey et al., to describe unique syndrome, clinically expressed during hypertensive and uremic encephalopathy, eclampsia, and immunosuppressive therapy. Hyperperfusion with resultant disruption of the blood-brain barrier results in vasogenic edema, but not infarction, most commonly in the parieto-occipital regions. The severity of this clinical symptom varies. For example, the visual disturbance can manifest as blurred vision, homonymous hemianopsia, or even cortical blindness.Patients may be mildly confused or agitated but can become comatose.Other symptoms less commonly seen include nausea, vomiting, seizures, and brainstem deficits.Chronic kidney disease (CKD) and acute kidney injury are both commonly present in patients with PRES. We are presenting a rare case of neurogenic bladder who developed PRES after augmentation cystoplasty due to underlying CKD.